WHAT DO RESIDENTS OF INFORMAL SETTLEMENTS THINK SOCIAL WORKERS SHOULD DO: VOICES FROM BHAMBAYI - Simpson, Barbara (Social Work/Maatskaplike Werk, 2003)
In 1992 the Centre for Social Work at the University of Natal established a community-based student unit at Bhambayi, an informal settlement some 25 kilometres north of the Durban city centre. Senior social work students, under the supervision of a member of the academic staff, offer a much needed social work service to this unique community. Students offer a variety of social work services. Individual casework services focus primarily on helping people to access grants and pensions and on specialist services for epilepsy, mental illness and mental handicaps. Child abuse, custody disputes and relationship problems are also dealt with. A children’s club provides a weekly meeting for primary school children and offers them the opportunity to socialise, learn arts and crafts, and to develop life skills. Community education programmes have been very successful, with the community participating enthusiastically in fun days, clean-up days and awareness programmes.